Techniques of Learning Planning Patterns Character Digitalization_Literacy 4.0 - Eka Vasia Anggis; Nur Laili (Universitas Wiralodra, 2022)
ABSTRACT Careful learning planning is important because if it is not prepared it will make the system less controlled. Learning planning must be adjusted to the quality and vision of the university and the demands for accreditation of study programs 4.0. Therefore, the purpose of this research is to create a learning planning design pattern technique with the character of digitization, literacy 4.0. The research method is (R&D). This research is a development research (R&D) with a 2-D model, namely Define and Design. Define stage, which is the initial research stage and information collection is carried out by investigating the desired needs in the field. Design stage planning stage (connecting all literature and component formats for presenting learning planning theoretically through literature review analysis. The conclusion is that research can produce learning planning products with digitalization, literacy and green campus paradigms 4.0 through analysis of literature studies from the desired aspects.